1976
DOI: 10.1099/00221287-95-2-353
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of Penicillin into Human Phagocytes Containing Neisseria gonorrhoeae: Intracellular Survival and Growth at Optimum Concentrations of Antibiotic

Abstract: S U M M A R YPhagocytes obtained from fresh human buffy coat (predominantly polymorphonuclear phagocytes) or from human buffy coat which had been incubated on a glass surface for I to 3 days (predominantly mononuclear phagocytes) were allowed to ingest gonococci, and then incubated with penicillin. More intracellular gonococci were killed at high than at low penicillin concentrations, indicating that penicillin penetrated the phagocytes. This was supported by autoradiography experiments with radiolabelled peni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1976
1976
1993
1993

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…However, it is not easy to demonstrate this protection phenomenon consistently; much depends, amongst other things, on the experimental techniques and upon the type of ingested micro-organism (see Veale et al, 1975Veale et al, , 1976Veale et al, and 1979. Whereas protection of an intracellular staphylococcal population obtained by simple washing procedures of extracellular bacteria was complete at a penicillin concentration of 1 pg/ml, the protection was only partial at 5 pg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not easy to demonstrate this protection phenomenon consistently; much depends, amongst other things, on the experimental techniques and upon the type of ingested micro-organism (see Veale et al, 1975Veale et al, , 1976Veale et al, and 1979. Whereas protection of an intracellular staphylococcal population obtained by simple washing procedures of extracellular bacteria was complete at a penicillin concentration of 1 pg/ml, the protection was only partial at 5 pg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Strain BSV was more resistant than strain BS to fresh human serum alone (Penn et al, 1975) and in the supernatants strain BSV seemed to be more resistant than strain BS to the bactericidal mixture containing penicillin ( Table 2 ) . In most cases, however, the supernatant counts at 2 10 4 h were so much lower than the deposit counts that the latter could only represent intracellular organisms (see Veale et al, 1976). * Electron microscopy indicated that most of these organisms were intracellular.…”
Section: Phagocytosis Of N Gonorrhoeae Grown In Vivo 347mentioning
confidence: 99%
“…One h after mixing (all experiments), and also at 15 and 30 min after mixing in some experiments, tubes were taken and the viable organisms in the supernatants and in the deposits attached to the glass were counted as described by Veale et al (1976). From the total number of phagocytes attached to the glass, the proportion of them containing gonococci, and the average number of gonococci ingested by them , the total gonococci visibly associated with phagocytes per slide was estimated.…”
Section: Phagocytosis Of N Gonorrhoeae Grown In Vivo 343mentioning
confidence: 99%
See 1 more Smart Citation
“…These were haemoglobin agar, described by Veale et al (1976), and a clear agar medium (AG agar) modified from that of Amies & Garabedian (1967) by Veale et al Subcutaneously implanted guinea-pig chambers. Male Dunkin-Hartley guinea pigs (grade 2; Olac, Banbury, Oxfordshire; 600 g) received two or four chambers (4 to 5 ml) which were implanted, inoculated and sampled as described by Veale et al (1975).…”
Section: Gonococcal Strain Grown In Vitromentioning
confidence: 99%